Contesting the terrain of the ivory tower : spiritual leadership of African-American women in the academy - Garner, Rochelle, 1962- (Studies in African American history and culture., 2004)
This study examines the leadership of three African-American women administrators in higher education, and how they have used their spirituality as a lens to lead in the academy.